Clarence Street, Ottawa: Contemporary Change in an Inner City 'Zone of Discard' - Tunbridge, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1986)
The principal focus of early Bytown, before it became the City of Ottawa and the capital of Canada, was the area now known as Lower Town. The elevation of the city's status led to a refocussing of development in the Centre Town area, south of Parliament, and Lower Town ultimately subsided into a classic 'zone of discard.' In recent years, such zones of discard in many North American cities have experienced a considerable renaissance, since they typically possess the oldest buildings remaining in the city and, as such major resources. This paper examines the evolution of Clarence Street, and puts its contemporary change into perspective; the focus is primarily upon the commercial section of the street. The central thesis to emerge from the paper is that the functional change now occurring in such revitalizing 'discard' areas does not necessarily imply a total change in their socioeconomic environment, and in particular their pattern of socioeconomic control.